SAT0317 Baseline MRA Predicts the Treatment Response to Vasodilator Udenafil in Patients with Secondary Raynaud's Phenomenon. (10th June 2014) - Park, J.K.; Moon, J.; Lee, E.Y.; Song, Y.W.; Lee, E.B.; Park, E.-A.
Abstract : Background: High-resolution MR angiography (HR-MRA) demonstrates blood flow in the digital arteries, which correlates with the severity of Raynaud's phenomenon (RP) Objectives: This study investigates whether baseline HR-MRA of the hand can predict the treatment response to udenafil, a new PDE5-inhibitor, in patients with secondary RP. Methods: Baseline MRA and Doppler ultrasound were obtained in 12 patients with secondary RP. The patients were treated with udenafil 100 mg/day for 4 weeks and changes in blood flow were measured. Blood flow on MRA was scored on a 4-point scale: 0, no visible flow; 1, visible flow to the proximal phalanx; 2, to the middle phalanx; and 3, to the distal phalanx. Peak systolic velocity (PSV) was measured to determine blood flow. Paired t-test and ANOVA were used to determine the treatment response of the different MRA scores. Trial registration: [www.clinicaltrials.gov, protocol number NCT01280266 ]. Results: On baseline MRA, 53.3% of digital arteries had an MRA score of 0, 25.8% MRA score of 1, 9.2% MRA score of 2, and 11.6% MRA score of 3. Overall, 4-week udenafil treatment improved digital flow (P<0.05) in all MRA scores. Digital arteries with MRA score 2 showed the best response with improvement in PSV by 14.5 mm/sec (P<0.01), whereas improvement in arteries of MRA scores 1 and 3 were not better than MRA scores of 0 (all, P>0.05). Conclusions: Digital arteries with moderate blood flow observed on MRA respond best to treatment with udenalfil. Therefore, baseline MRA may help predict treatment response in patients with secondary RP. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2186